Development of Metaverse Learning Modules based on Local Wisdom with a Deep Learning Approach to Improve Students' Literacy Skills in Elementary Schools - Suttrisno, Suttrisno; Yulia, Nurul Mahruzah (LP. Ma'arif Janggan Magetan, 2025)
The literacy skills of elementary school students remain relatively low due to the lack of contextual and interactive learning media. This study aims to develop a metaverse-based learning module that integrates Bojonegoro local wisdom with a deeplearning approach to improve students' literacy skills. The research employed a Research and Development (R&D) method with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects were 30 third-grade elementary students in Bojonegoro. Data were collected through observation, interviews, questionnaires, and literacy tests, and analyzed both qualitatively and quantitatively. Expert validation indicated that the module is highly feasible, with media scoring 92%, language 94%, and content 95%. A small group trial (10 students) showed an improvement in literacy scores from 40% to 70%, while a large group trial (20 students) showed an increase from 45% to 85%. Student responses were very positive (86%). The N-gain result of 72.9%–81.4% indicated medium to high effectiveness. The module has proven effective in improving literacy comprehension while strengthening students' cultural identity. This research product is recommended for broader implementation in IPAS learning at elementary schools. This study developed a metaverse-based learning module integrating local wisdom and a deeplearning approach to enhance elementary students’ literacy skills, proving effective in improving learning outcomes, motivation, and engagement through interactive, adaptive, and culturally contextual learning experiences.”